A proactive greedy routing protocol precludes sink-hole formation in wireless sensor networks - Mustafa, Mayada S. A.; M Ali, Borhanuddin; Rasid, MFA; Hashim, Shaiful J.; Saeed, I. A. (AIRCC Publishing Corporation, 2022)
A tree topology is a commonly employed topology for wireless sensor networks (WSN) to connect sensors to one or more remote gateways. In many-to-one traffic, routing imposes a heavy burden on downstream nodes, as the same routes are repeatedly used for packet forwarding from one or more sensor chains. The challenge is traffic paths that ensure balanced energy consumption at sink-hole to protect sensors from fast death. This paper proposes an energy consumption pattern-aware greedy routing protocol that proactively protects many-to-one topology from the sink-hole formation. The proposed protocol, Energy Balance-Based Energy Hole Alleviation in Tree Topology (EBEHA-T), precludes energy hole formation rather than retrospectively responding to a hole detection. Updated status of variations in energy consumption patterns at the sink-hole and construction feature of joint nodes in the tree topology aids in routing decision. Performance evaluation of EBEHA-T against benchmark method RaSMaLai shows increased energy-saving across the entire network and a marked improvement in energy consumption balance in energy hole zones. This precludes energy hole formation and the consequent network partitioning, leading to improved network lifetime beyond that of the RasMaLai.